Explorations on the history of state intervention in the Philippine economy the role of public enterprises - Tabbada, Jose P. (Philippine Journal of Public Administration, 1985)
The article describes the changing nature, scope and role of the Philippine state through the various periods of the country's history, particularly as manifested in the existence and development of state enterprises. From a limited state during the American colonial period, the Philippine state has, by the seventies, assumed a very central role in the economy, especially in entrepreneurship. It is suggested that changes in the nature and role of the Philippine state may be understood by reference to certain underlying social forces, such as the state of the economy and the strength of the domestic capitalist class.